Molecular identity of cyanobionts and mycobionts in Peltigera membranacea - Iglesias Fernández, Vanessa, 1986- (2010)
Ritgerðin er lokuð til júlí 2011 Cyanobacteria of the genus Nostoc are widespread in nature and occur both in a free-living state as well as in symbiotic associations, most prominently with fungi in lichens and leguminous plants (1). A molecular phylogenetic approach was used to investigate whether specific types of Nostoc associate with different samples of lichenizing Peltigera fungi or whether fungal spores from different lichens species can associate with one or several widespread strains of symbiotic Nostoc. The phylogenetic analysis was conducted on 16S ribosomal RNA genes from symbiotic strains of Nostoc and the Internal Transcribed Spacer (ITS) sequences of fungal rDNA. Samples of the lichen Peltigera membranacea were identified and collected from different places in Iceland, mainly around Reykjavik between 2008- 2009. The prokaryotic 16S ribosomal RNA gene and the eukaryotic Internal Transcribed Spacer rDNA region fragments were amplified by the polymerase chain reaction from DNA extracted directly from the collected lichens, and sequenced directly. DNA extracted from lichen apothecia was also used for the ITS study. The results confirmed that 16S ribosomal RNA gene sequences were identical between lichen specimens in Iceland but not in other geographical areas such as Canada and U.S.A. The initial results from ITS sequences revealed heterogeneity in the mycobiont population of Peltigera membranacea in Iceland. But, still it needs more thorough ITS analysis to confirm this.